The Role of Mens Rea as a Condition for Punishment: A Case Study of Tom Lembong from the Perspective of Indonesian Criminal Law - Haznul, Fikry (KRTHA BHAYANGKARA, 2025)
This study examines the centrality of mens rea as a requirement for criminal liability in Indonesian corruption cases, focusing specifically on the case of Tom Lembong. The challenge of proving criminal intent or the mental state of the perpetrator presents a significant issue within Indonesia's criminal justice system, particularly when judicial verdicts contradict the lack of clear evidence regarding the defendant's subjective element. The research aims to analyze the position of mens rea in Indonesian criminal law, review the mechanisms for establishing the mental element in corruption cases using a case study approach, and evaluate the legal implications of the absence of proof of mens rea for fair criminal responsibility. Employing a systematic literature review, the study synthesizes scholarly articles, court decisions, and relevant policy documents from the last five years, selected through strict criteria and thematic analysis. The findings demonstrate that, in corruption cases, the proof of the mens rea element is often overlooked, leading to convictions that do not always reflect the principle of geen straf zonder schuld and thus risk undermining substantive justice. This research offers a critical mapping of the evidentiary standard for mens rea, highlights the relevance of abolition as a systemic corrective mechanism, and provides innovative recommendations for courts and policymakers to more clearly distinguish between administrative motives and criminal intent, thereby promoting a more adaptive and just legal enforcement